2020
DOI: 10.1021/acssuschemeng.0c03432
|View full text |Cite
|
Sign up to set email alerts
|

Selective Product Crystallization for Concurrent Product Separation and Catalyst Recycling in the Isomerizing Methoxycarbonylation of Methyl Oleate

Abstract: Selective product crystallization proved to be a very attractive recycling strategy for homogeneous catalysts. This approach was demonstrated for the Pd-catalyzed isomerizing methoxycarbonylation of the renewable oleochemical methyl oleate using technical-grade starting material. The corresponding product, dimethyl-1,19-nonadecanedioate, is a valuable linear platform chemical for biobased polycondensates. A pure product phase (>96%) was produced by selectively controlled cooling crystallization following the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 36 publications
0
15
1
1
Order By: Relevance
“…5) that find wide application as commodity chemicals, 171 biodiesel fuel, 172 and as intermediates for further chemical diversification. [173][174][175][176][177] In particular, epoxidized fatty acid esters (EFAs, Fig. 5) can be easily obtained and display potential for applications such as lubricants, additives and plasticizers.…”
Section: Fatty Acid Based Carbonatesmentioning
confidence: 99%
“…5) that find wide application as commodity chemicals, 171 biodiesel fuel, 172 and as intermediates for further chemical diversification. [173][174][175][176][177] In particular, epoxidized fatty acid esters (EFAs, Fig. 5) can be easily obtained and display potential for applications such as lubricants, additives and plasticizers.…”
Section: Fatty Acid Based Carbonatesmentioning
confidence: 99%
“…In contrast to the other recycling approaches, there is no need for any auxiliary (solvent, support, etc. ), contributing to Green chemistry . The linear product selectively crystallizes upon cooling the reaction mixture.…”
Section: Stability Of 12-dtbpmb and Recycling Approaches In Carbonyla...mentioning
confidence: 99%
“…This approach was recently extended to a recycling technique by Seidensticker and co-workers (see section 6). 130 By subsequent reduction, initially with LiAlH 4 and polycondensation, a linear polyester was obtained (Figure 24). 131 This biobased polyester synthesis and application of the products was patented in 2013.…”
Section: Synthesis Of αω-Bifunctional Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous works showed that selective product crystallization is very efficient for purification in the methoxycarbonylation. [27,28] Thereby, auxiliaries are avoided. Regarding this work, methyl 9,10-dihydroxystearate also exhibits a high boiling point of 70 °C [29] and low solubility in suitable solvents, offering the broad potential for purification as a stable intermediate and subsequent application in other reactions, such as oxidative cleavage toward other value products.…”
Section: Introductionmentioning
confidence: 99%